Computational Study of Scorpion Venom (Lychas Mucronatus) Activity as Antimicrobial Peptides (AMPs) to the SARS-CoV-2 Main Protease for the Future Coronavirus Disease (COVID-19) Inhibitors - Taufik Muhammad Fakih (Universitas Jenderal Soedirman, 2021)
The 2019 coronavirus pandemic disease (COVID-19) is still declared a global pandemic by the World Health Organization (WHO). Therefore, an effort that is considered effective in finding therapeutic agents is needed to prevent the spread of COVID-19 infection. One of the steps that can be chosen is by utilizing antimicrobial peptides (AMPs) from animal venom by targeting the specific receptor of SARS-CoV-2, namely the main protease (Mpro). Through this research, a computational approach will be conducted to predict antiviral activity, including protein-peptide docking using PatchDock algorithm, to identify, evaluate, and explore the affinity and molecular interactions of four types of antimicrobial peptides (AMPs), such as Mucroporin, Mucroporin-M1, Mucroporin-S1, and Mucroporin-S2 derived from scorpion venom (Lychas mucronatus) against main protease (Mpro) SARS-CoV-2. These results were then confirmed using protein-peptide interaction dynamics simulations for 50 ns using Gromacs 2016 to observe the molecular stability to the binding site of SARS-CoV-2 Mpro. Based on protein-peptide docking simulations, it was proven that the Mucroporin S-1 peptides have a good affinity against the active site area of SARS-CoV-2 Mpro, with an ACE score of −779.56 kJ/mol. Interestingly, Mucroporin-S1 was able to maintain the stability of its interactions based on the results of RMSD, RMSF, and MM/PBSA binding free energy calculations. The results of the computational approach predict that the Mucroporin-S1 peptide is expected to be useful for further research in the development of new antiviral-based AMPs for the COVID-19 infectious disease.